Penggunaan Media Pembelajaran Pendidikan Jasmani, Olahraga, dan Kesehatan Oleh Guru Sekolah Dasar Se-kecamatan Teluk Betung Selatan Pasca Pandemi Covid-19 - Bambang Haryono; H Herpratiwi; Frans Nurseto Subekti (Universitas Sarjanawiyata Tamansiswa, 2022)
This study aims to describe the application of Sports physical Education and health learning media by teachers in Teluk Betung District after the covid-19 pandemic. This type of research is quantitative descriptive research with survey method. The population in this study were all teachers in Teluk Betung District with a sample of 20 teachers who were taken using purposive sampling technique. Data collection techniques with observation and questionnaires. The data analysis technique uses descriptive percentage analysis. The results of this study indicate that the use of Sports physical Education and health learning media by teachers in elementary schools throughout Teluk Betug sub-district is in the very low category 25%, low 16,67%, moderate 25%, high 33,33% and very high 0%.